ASSESSMENT OF THE MEDICINAL PROPERTIES AND COMPONENTS OF THE BLEND OF THREE INDIGENOUS ESSENTIAL OILS (Syzygium aromaticum, Monodora myristica, AND Xylopia aethiopica) FROM AFRICA - Awojide, Shola Hezekiah; Adeyemo, Abayomi Gideon; Adeyemo, Aminat Adebola; Blessing , Elijah Titilayo; Anifowose, Adebanjo Jacob; Oladipo-Olalekan, Omolara; Adeniyi, Emmanuel Oluwafemi; Abdulazeez, Ummuhani Titilayo (Bulletin of Natural Sciences Research, 2025)
The essential oils of Syzygium aromaticum, Monodora myristica, and Xylopia aethiopica have been used widely in Africa for medicinal purposes. This work is aimed at finding out the combined medicinal efficacy of the three essential oils. The crude EOs were extracted by the hydrodistillation method. The chemical components were determined by GC-MS analysis. The phytochemicals, antidiabetic, anti-inflammatory, and antioxidant activities were determined by standard analytical methods. The GC-MS analysis indicated eugenol (75.08%) as the major component in the EO of S. aromaticum, isocaryophyllene (29.36%) in the EO of M. myristica, isospathulenol (8.67%) in the EO of X. aethiopica, and eugenol (34.25%) in the blend of the EOs. The phytochemicals in all the EOs and the blend were at varying values. α-amylase and α-glucosidase inhibition showed that the EO blend with an IC50 value of 1250.69 µg/mL and 1080.56 µg/mL, respectively, had the highest inhibition compared with other EOs. S. aromaticum had the highest activity against the anti-inflammatory indicators. The least inhibitory activity for DPPH was recorded with M. myristica EO. S. aromaticum recorded the highest inhibitory efficacy against ABTS and nitric oxide assays, respectively. The blend recorded the highest inhibitory activity against lipid peroxidation, with an IC50 value of 827.22 µg/mL. The findings demonstrated that the crude EOs and the blend exhibited medicinal activities. However, the EO blend had higher potency.
Keywords: Essential oil; Blend; Antioxidant; Anti-inflammatory; Anti-diabetic